0442 Improved resilience following Cognitive Behavioral Therapy for Insomnia mediates treatment outcomes and protects against long-term insomnia and depression. (25th May 2022) - Cheng, Philip; Kalmbach, David; Hsieh, Hsing-Fang; Castelan, Andrea Cuamatzi; Sagong, Chaewon; Drake, Christopher
Abstract: Introduction: While the negative consequences of insomnia are well-documented, a strengths-based understanding of how sleep can promote health promotion is still emerging and much-needed. Correlational evidence has connected sleep and insomnia to resilience; however, this relationship has not yet been experimentally tested. This study examined resilience as mediator of treatment outcomes in a randomized clinical trial with insomnia patients. Methods: Participants were randomized to either digital Cognitive Behavioral Therapy for insomnia (dCBT-I; n=358) or sleep education control (n=300), and assessed at pre-treatment, post-treatment, and one-year follow-up. A structural equation modeling framework was utilized to test resilience as a mediator of insomnia and depression. Risk for insomnia and depression was also tested in the model, operationalized as a latent factor with sleep reactivity, stress, and rumination as indicators (aligned with the 3-P model). Sensitivity analyses tested the impact of change in resilience on the insomnia relapse and incident depression at one-year follow-up. Results: dCBT-I resulted in greater improvements in resilience compared to the sleep education control. The improved resilience was a significant mediator of reduced insomnia and depression severity following treatment. Furthermore, improved resilience following dCBT-I also reduced insomnia and depression at one-year follow-up by lowering latent risk. Sensitivity analyses indicated that each point improvement in resilience following treatment reduced the odds of insomnia relapse and incident depression one year later by 76% and 65% respectively. Conclusion: Improved resilience is a contributing mechanism to treatment gains following dCBT-I and may further protect against longer-term insomnia and depression by reducing risk. Support (If Any): K23HL138166; R01HL159180